SHARING EXPERIENCE ON THE ACTIVITY OF TRAINING CENTRE “FOREIGN LANGUAGES FOR SPECIFIC PURPOSES” AT THE DEPARTMENT OF LINGUISTICS OF SHEE “IVANO-FRANKIVSK NATIONAL MEDICAL UNIVERSITY” - Цебрук, І. Ф.; Венгринович, Н. Р. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
The article deals with coverage of working experience of the training center for in-depth study of the English, German and French languages by the scientific and pedagogical staff of SHEE "Ivano-Frankivsk National Medical University."